Plantinga on Exclusivism: (transl. Marcin Iwanicki) - Feldman, Richard; Iwanicki, Marcin (Roczniki Filozoficzne, 2025)
Exclusivists contend that specific doctrines, such as Christian doctrines, are true and those incompatible with them are false. In “Pluralism: A Defense of Religious Exclusivism” Alvin Plantinga defends religious exclusivism from a variety of objections. In this paper I discuss one of those objections. Plantinga agrees, at least for the sake of argument, that those in other religious traditions have evidence for their beliefs comparable to his evidence for his beliefs. Some critics contend that in maintaining their beliefs in the light of this fact about equality of evidence, exclusivists are not treating like cases alike. The critics think that if you know that someone else’s evidence for their belief is just as good as your evidence for your incompatible belief, then you are not reasonable in retaining your belief. I argue, in opposition to Plantinga, that a version of this principle is correct.